Rural Tourism, Agri Tourism; Sebuah Penelusuran Literature - Khaeril, Khaeril; Mohungo, Yolanda; -, Laela (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2021)
Village are the smallest community entities that exist in a state structure. There are many problems faced, for example poverty, inadequate basic infrastructure, less skilled human resources, insufficient employment opportunities. Tourism village - Agri tourism is expected to be a solution to dealing with classic problems that exist in rural areas. This article aims to identify research gaps in the field of study of tourism villages in a systematic search, identify reference authors in the field of Rural Tourism, agri-tourism., Identify the theories used in the Tourism Village article. The article implements a qualitative method with the Literature review method with the help of the Perish Publish Program to compile the data script and Vos Viewer is used to analyze the data. The results show that there is an opportunity to continue studying tourism villages, especially with regard to sustainable development, involvement of local communities and development / development of tourist villages, adopting ICT for tourism villages in order to improve performance and tourism visits, and alleviate poverty. Also obtained are several authors who become references in the study of tourist villages. There are also 13 theories used in studying tourism villages and agritourism, this shows that the tourism village as an object of study is still open to being in and is very dynamic in its development.